Efeito do 5-Fluorouracil na reabsorção óssea alveolar induzida por ligadura em ratos - Barbosa, Thayanne Brasil (2015)
Introduction: 5-fluorouracil (5-FU) is a highly used anticancer drug. Its administration causes several side effects and. its role in bone loss has been recently studied, since 5-FU showed a decrease in bone mineral density and growth inhibition in young rats. The aim of our study was to investigate the effect of 5-FU on the in ligature-induced bone resorption in rats. Methods and results: 146 Wistar rats (180-220 g) were divided in four groups that received distilled water (2 ml/kg, IP) or 5-FU (37.5, 75 or 150 mg/kg, IP 1 hour before the ligature placement. Sacrifice was performed at 11th day. Hemiarcades were submitted to macroscopic (mm²), histologic or histometric (mm²) analyses. In addition, cytokines (TNF-α and IL-1β; pg/mg) were dosed and the assessment of MPO activity (U/mg) and total and bone-specific alkaline phosphatase (U/ml) was performed. Survival, leukogram, body mass variation and liver, kidney and spleen conditions were also evaluated. p<0.05 was considered significant. The study was approved by the ethics committee in animal research. Ligature placement caused an important alveolar area bone loss, including the furcation area. It also caused an increase in the MPO activity, in the concentrations of TNF-α e IL-1β, and diminished bone-specific alkaline phosphatase. It was observed greater furcation lesions, alveolar bone destruction and an increase in the inflammatory infiltrate when compared to normal (p<0.05). Although 5-FU did not increase MPO activity when compared with NT, it promoted an exacerbation of the periodontal destruction, with a severe alveolar bone loss, including the furcation area when compared with NT (p<0.05). Another finding was the increased concentration of TNF-α e IL-1β. In addition, 5-FU groups presented lower values of bone-specific alkaline phosphatase when compared to normal (p<0.05). It was also observed a severe destruction of the periodontum and a marked inflammatory infiltrate. Systemically, 5-FU (150 mg/kg) caused neutropenia, diminished rate of survival and loss of weight. Finally, it was not observed alterations in the hepatic, renal, or splenic conditions. Conclusion: Briefly, 5-FU increased ligature-induced bone resorption and the concentration of TNF-α and IL-1β, cytokines that are involved in the bone resorption process. Neutropenia was caused by the administration of the drug and contributed to exacerbate the destruction of the periodontium.